Biomass and Habitat Use of Guinea Fowl (Numidia meleagris) in Dinder Biosphere Reserve, Sudan, during the Dry Season* (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted in the Dinder Biosphere Reserveduring the dry seasons of 2007 and 2008. The objective of the study wasto determine biomass and habitat use of Guinea fowl (Numidia meleagris)in the various ecosystems of the reserve. Loop and nearest neighbourmethods were used for measuring the vegetation attributes. The density ofGuinea fowl was calculated in strip transects that were 500 m long and200 m wide by the double sampling procedure. First, the number ofGuinea fowl was estimated and then counted directly. Second, apredictive model was developed from the relationship between thecounted and the estimated variables. Subsequently, the number of thebirds was only estimated and the actual count was predicted from themodel. Guinea fowl was captured by mist nets and locally made traps,weighed and morphometric measurements were taken. Biomass wascalculated as the product of density and the live weight. The density ofGuinea fowl was high around the mayas (meadows) and riverineecosystems. The total biomass in the reserve was 93.76 kg/km². Thevegetation attributes around the mayas varied considerably. Thepercentage of litter was high in some mayas and low in others; bare landwas relatively high in most of the reserve area but burnt areas were verylow. Trees of high densities included Acacia seyal, Combretum sp.,Balanites aegyptiaca, Ziziphus-spina-christi and Acacia polycantha. Ofthese, Guinea fowl roosted only on A. seyal and Combretum sp.
Keywords: Guinea fowl; habitat; biomass; Dinder biosphere reserve